Structural and magnetic properties of the low-dimensional fluoride β-FeF3(H2O)2·H2O. Issue 31 (21st August 2015) - Nénert, Gwilherm; Fabelo, Oscar; Forsberg, Kerstin; Colin, Claire V.; Rodríguez-Carvajal, Juan
<x xml:space="preserve">Abstract</x> We have reinvestigated the crystal structure of the low-dimensional fluoride β-FeF3(H2O)2·H2O using high resolution neutron and X-ray diffraction data.